Provincial Overdose Cohort: Population Data Linkage During an Overdose Crisis - Chloé Xavier; Bin Zhao; Wen Qi Gan; Amanda Slaunwhite (International Journal of Population Data Science, 2020)
Introduction In 2016, the Provincial Overdose Cohort (ODC) was created following the declaration of the public health emergency in British Columbia (BC), Canada. The ODC is a set of longitudinal and linked administrative data which identifies illicit drug-related overdose events, including death, ambulance, emergency room, hospital, physician, and prescription drug records.